Shared mechanism underlying unembedded and embedded enrichments: Evidence from enrichment priming - Sun, Chao; Breheny, Richard (Proceedings of Sinn und Bedeutung, 2019)
In this paper, we use a priming paradigm to explore the mechanisms underlying unembedded and embedded scalar enrichments. In particular, the aim is to see if local pragmatic enrichment could be a shared mechanism, involved in both. The two experiments presented adopt Bott & Chemla's (2016) enrichment priming paradigm and test whether unembedded and embedded enrichments could prime each other. The goal is to investigate whether local pragmatic enrichment is indeed being accessed for the interpretation of the unembedded scalar and whether local enrichments, like other lexical semantic phenomena, are susceptible to priming.